2019
DOI: 10.1186/s12911-019-0790-3
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and rapid screening model for potential diabetes mellitus

Abstract: BackgroundPrediction or early diagnosis of diabetes is crucial for populations with high risk of diabetes.MethodsIn this study, we assessed the ability of five popular classifiers (J48, AdaboostM1, SMO, Bayes Net, and Naïve Bayes) to identify individuals with diabetes based on nine non-invasive and easily obtained clinical features, including age, gender, body mass index (BMI), hypertension, history of cardiovascular disease or stroke, family history of diabetes, physical activity, work stress, and salty food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…The DLM included seven NIVs (age, male gender, hypertension, family history of diabetes, smoking status, BMI, and waist circumference) that would be convenient for a layperson to use as a self-assessment of diabetes risk in the real world. These variables are highly correlated with undiagnosed diabetes in other studies [38][39][40][41][42][43][44][45]. Although blood analysis (including FPG and oral glucose tolerance test) are required to diagnose at-risk individuals based on the guidelines, our model can provide users with an estimation of their diabetes status without a medical diagnosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The DLM included seven NIVs (age, male gender, hypertension, family history of diabetes, smoking status, BMI, and waist circumference) that would be convenient for a layperson to use as a self-assessment of diabetes risk in the real world. These variables are highly correlated with undiagnosed diabetes in other studies [38][39][40][41][42][43][44][45]. Although blood analysis (including FPG and oral glucose tolerance test) are required to diagnose at-risk individuals based on the guidelines, our model can provide users with an estimation of their diabetes status without a medical diagnosis.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the development of disease prediction or screening models should be user-centric. Pei et al developed a diabetes prediction model using non-invasive variables based on machine learning algorithms (decision tree, AdaBoost, support vector machine, Bayesian network, naïve Bayesian) that showed an appropriate performance [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several types of machine-learning algorithms, including instance-based ( Esteban et al, 2017 ; Kagawa et al, 2017 ; Nilashi et al, 2017 ; Pei et al, 2019 ; Talaei-Khoei & Wilson, 2018 ), decision trees ( Alghamdi et al, 2017 ; Esteban et al, 2017 ; Pei et al, 2019 ; Talaei-Khoei & Wilson, 2018 ), artificial neural network ( Esteban et al, 2017 ; Nilashi et al, 2017 ; Talaei-Khoei & Wilson, 2018 ), ensemble ( Alghamdi et al, 2017 ; Esteban et al, 2017 ; Pei et al, 2019 ), Bayesian ( Alghamdi et al, 2017 ; Anderson et al, 2015 ; Esteban et al, 2017 ; Maniruzzaman et al, 2017 ; Pei et al, 2019 ), statistical model ( Alghamdi et al, 2017 ; Esteban et al, 2017 ; Maniruzzaman et al, 2017 ; Talaei-Khoei & Wilson, 2018 ; Wu et al, 2018 ), and others (see Table 1 ), have been adopted to predict T2DM-related issues. However, these studies revealed different results in predicting the onset of T2DM even with the same machine-learning algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Pei et al (2019) and Alghamdi et al (2017) both adopted J48 as one of their algorithms for predicting the onset of T2DM, only Pei et al (2019) found that J48 had the best performance. The performance of support vector machine also differs among opposing studies ( Esteban et al, 2017 ; Kagawa et al, 2017 ; Nilashi et al, 2017 ; Pei et al, 2019 ; Talaei-Khoei & Wilson, 2018 ). Further, not all inclusionary studies adopted the same algorithms, making it difficult to accurately compare the performance of differing algorithms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation